Impact of venous thromboembolism during admission for meningioma surgery on hospital charges and postoperative complications. (January 2019) - Spinazzi, Eleonora F.; Shastri, Darshan; Raikundalia, Milap; Silva, Nicole A.; Eloy, Jean Anderson; Liu, James K.
Highlights: Venous thromboembolism occurred in 2.1% of inpatient admissions undergoing meningioma resection. Length of stay was an average of 18.8 days with hospital charges of $195, 837 following venous thromboembolism. Venous thromboembolism patients were more likely to be older and more commonly male. Patients with venous thromboembolism experienced significantly higher rates of post-operative complications. Abstract: Surgical resection of meningiomas has been associated with high rates of venous thromboembolic events (VTE) as compared with all other intracranial tumors. There is a paucity of data regarding the clinical complications and comorbidities associated with this cohort yet the underlying pathophysiological mechanism for this tumor-specific finding remains unclear. Our goal was to determine the various impacts of VTE on meningioma surgery in a large cohort of inpatient admissions. This retrospective analysis utilized discharge data from the National Inpatient Sample (NIS) from 2002 to 2010. Patient demographics, comorbidities, length of stay, hospital charges, and postoperative complications were compared between patients with and without VTE. Of 20, 259 patients, 426 (2.1%) experienced a VTE. Compared to the non-VTE cohort, patients that experienced a VTE were older (62.7 ± 13.7 vs. 57.2 ± 14.7; p < 0.001), were more commonly male (38.0% vs 30.1%; p = 0.001), had longer hospitalizations (18.8 vs 6.6 days; p < 0.001), and incurred significantly greater hospital charges ($195, 837 vs $74, 434; p < 0.001). VTE patients experienced significantly higher rates of acute postoperative complications including shock, hemorrhage, wound dehiscence, infection, intracerebral hemorrhage, hemiparesis/hemiplegia, stroke, and death during admission. Odds ratio of aforementioned postsurgical complications remained significantly higher both before and after adjusting for age and sex (all p < 0.01). Occurrence of VTE in patients undergoing meningioma resection portends greater hospital charges, most likely attributed to longer lengths of admission. Increased postoperative complications and mortality in the VTE group warrants further investigation and wariness of the surgeon when treating surgical candidates of meningioma.